ffect of Extraction Methods on Bioactive Compounds of Plant Origin - Erinç Koçak; Fikret Pazır (Turkish Journal of Agriculture: Food Science and Technology)
The use of bioactive compounds has been maintaining its significance from nutritional aspects. Due to the increasing demand for them in potential markets, researchers struggle to create new sources and improve their methods. Plant materials possess plenty and a diverse range of these compounds. However, their availability strongly depends on the extraction techniques in addition to the sampling methods and the applicability of the method to the specific parts of the plant. Thus, it is crucial to develop a common, precise way which will enable to extract all the active components regardless of their origin and their location in the plant material. Besides, the new method ought to have the highest economic value in comparison to the present applications which means that the efficiency of the extraction should be acceptable on industrial scale as well. Even though numerous methods have been improved so far, it seems to be unlikely to achieve a standardized solution with high valorization for the extraction of bioactive compounds from plants until now. This review aims to discuss the novel extraction methods in addition to the conventional techniques focusing on the critical parameters such as the cost, time, yield, feasibility and eco-friendliness of the process.